Shock Reduction Technique on Thin Plate Structure by Wave Refraction Using an Elastic Patch. (6th December 2021) - Hwang, Dae-Hyun; Han, Jae-Hung
Abstract : In general, bending waves transfer the largest portion of shock energy in a plate-like structure. This study proposes a new shock reduction method using an elastic patch designed to defocus the bending waves through the refraction of the waves so that it is possible to effectively reduce the propagating shock for a certain target area. Elastic patches of three different shapes were considered. The shock reduction performance of these patches was analytically, numerically, and experimentally investigated and compared. All results consistently showed that attached patches can effectively reduce passing waves for areas behind patches. Therefore, utilizing the proposed methods, we can reduce the transient shock response at certain target areas of various practical structures without degradation of structural stiffness or strength simply by bonding with an elastic patch.